Gambaran Arus Puncak Ekspirasi Pada Penderita Asma Di Wilayah Kerja Puskesmas Mujur: Description of Peak Expiratory Flow in Asthma Patients in the Working Area of the Mujur Health Center - Laily Widya Astuti (Public Health and Safety International Journal, 2022)
Asthma is one of lung diseases caused by inflammation, it causes the asthma sufferers to experience breath difficulty which results in the decrease of PEF (Peak Expiratory Flow) scores. The purpose of this research was to obtain knowledge about PEF on asthma sufferers in Puskesmas Mujur. The method of this research was descriptive with design cross sectional. There were 38 respondents as samples of this research for two weeks. An instrument applied in this research was peak flow meter to measure PEF scores of patients. The result of this research showed that twenty-five respondents PEF scores (65.6%) are in red zone (<50%) and thirteen people (34.4%) are in yellow zone (50%). The conclusion of this research is that peak expiratory flow decreases in patients suffering asthma.